PENGARUH VARIASI KOMPOSISI PASIR POZZOLAND DAN PASIR ALAM TERHADAP KUAT TEKAN DAN KUAT LENTUR BATA RINGAN - Hermila Hermila (Department of Physics – Universitas Negeri Padang UNP, 2014)
The purpose of this research is to investigate what is the variation of composition between pozzoland sand and natural sand as bricklayers light material that can result in compressive strength and flexural strength best. In this study, the method used is the experimental method, the independent variable in this study is a variation of composition pozzoland sand and natural sand sieve no.8 bricklayers light. The making of sample is done by testing the compressive strength and flexural strength from the age of 14 days, 21 days, and 28 days. From this research found the effect variations in composition pozzoland sand and natural sand in the manufacture of lightweight brick is the more variations in composition of pozzoland sand then natural sand, so compressive strength and flexural strength lightweight bricks produced is increasing, and the higher the age of light brick, so the compressive strength and strong bending is also increasing. It means the pozzoland sand greatly affect the compressive strength and flexural strength in a lightweight brick. Keywords: Sand pozzoland, natural sand, compressive strength, flexural strength, lightweight bricks